Multi-time Scale Voltage-Reactive Power Control for Distribution Network with Distributed Generation - LIU Haotian; ZHENG Chuyu; LENG Yang; LI Qin; ZHANG Hua; CHEN Shidu; LI Jiayong (Journal of Harbin University of Science and Technology, 2024)
Aiming at the problems of network loss increase, voltage deviation and voltage exceeding specified limits when large- scale distributed generations ( DGs) connected to distribution network ( DN) , this paper proposes a multi-time scale coordinated control method considering different types and response speeds of reactive power regulation equipment. In day-ahead stage, an optimization model is established to minimize the network loss and voltage deviation, by controlling traditional equipment like tap changers and capacitor banks, which is efficiently solved by linearization and second-order cone algorithm. In real-time stage, a reactive power-voltage control model based on the voltage sensitivity principle is proposed, which considers the differences in the adjustment costs of different DGs. The simulation example shows that the proposed method reduces the voltage deviation and network loss (by 34. 73% ). And for the voltage regulation, it can optimize the regulation target according to the voltage sensitivity and the regulation costs of each DG, and thus has better economic performance while adjusting voltages.